Using the nominal group technique to design an appropriate communication strategy among strategic procurement and internal stakeholders - Lenarčič, Božidar (Organizacija (Kranj), 2024)
Background/Purpose: The implementation process of the procurement strategy requires consensus among in - ternal stakeholders. An effective procurement strategy aligns with specific business requirements and accommo- dates the individual introversion of internal stakeholders. From the latter, we formulate our research question: How is the classification of internal procurement stakeholders designed in the validation of the procurement strategy? The research objective is to present the result in the form of a schematic description and a recommendation for a communication strategy, based on insights from existing theoretical knowledge and the formulation of professional references. Methods: Nominal Group Technique (NGT) with 13 participants has been applied to analyze viewpoints on pro - curement functions. To ensure reliability and validity, Cronbach’s alpha test, Spearman coefficient, and t-tests have been used. Results and Conclusion: Study categorizes internal procurement stakeholders into four groups based on their stance towards strategy implementation: positive, cautiously positive, negatively independent, and negative stake - holders. For each group, we recommend a tailored communication strategy that includes elements such as inform - ing, guiding, motivating, and providing credible data. The research results offer important insights into the dynamics among organizational stakeholders and how communication impacts the success of strategy implementation. We have found that under-standing and adapting to various types of stakeholders are crucial for success, from those highly involved and positively inclined to those with the potential to oppose or hinder implementation. Employing specific communication strategies for each group can significantly enhance the chances of successful implementa- tion and sustainable execution of strategies.
Keywords: communication strategy; internal communication; internal stakeholder management; komunikacijska strategija; management; nabava; nominal group technique; notranja komunikacija; poslovni procesi; procurement strategy